Italian Politics and Albanian National Movement in the end of XIX-th and the Begining of the XX-th - Tare, Denisa (Richtmann Publishing, 2011)
The end of the XIX-th and the beginnings of the XX-th present an important period for the Albanian folk. During this periodincreased the efforts to be acquainted nationally. Due the sublimation of the Albanian national conscience, will be considered thelightening of the minds, which it will be possible only through the national education. An important part, in this process had theArberesh of Italy. This thesis is going to treat their contribute in favor if the national question. The Arberesh area had the same behaviorin the formation’s political attitude of the Italian government toward Albania and the Albanian’s question in total. A special merit tothe inauguration of active politics toward east Adriatic, e especially toward Albania and the Albanian it had, no doubt, the ItalianPrime Minister Francesco Crispi, originally Arberesh. His politic vision looked over the Italian government interests, to increase theinfluence of the peninsula of Balkan e especially in Albania, although inside this frame, he gave his contribute stimulating the efforts ofhis coexistent to the freedom and the social progress. The project of Italy inaugurated by Crispi aimed to have a main position in OtrantoChannel, possibility to allow it to penetrate in Ballkan to expand the influence area into Adriatic and Jon. This essay discusses over theproblematic over mentioned giving us a clearer panorama over Albania of the National Renaissance period, the challenges it affronted,which, without doubt, it was possible to be resolved with the valuable contribute of the Albanians of Diaspora.